2021
DOI: 10.3389/fphar.2021.657033
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Modulation of Ferroptosis and Its Role in Central Nervous System Diseases

Abstract: Ferroptosis is a new form of programmed cell death characterized by intracellular iron-dependent accumulation of lipid peroxide and primarily associated with iron metabolism, glutathione-dependent pathway, and coenzyme Q10-dependent pathway. Recent studies demonstrate that ferroptosis is associated with central nervous system (CNS) diseases, such as stroke, Parkinson’s disease, Alzheimer’s disease, and Huntington’s disease. This review summarizes the key regulatory mechanisms of ferroptosis and its role in CNS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 110 publications
(134 reference statements)
0
26
0
Order By: Relevance
“…Cystine is reduced to cysteine to participate in GSH synthesis by system Xc - ( 60 ). The transport process of this system does not require ATP, and it is mediated by the difference in the concentration of amino acids presenting on both sides of the cell membrane ( 61 ). GSH is a tripeptide comprising glutamate, cysteine, and glycine.…”
Section: Molecular Mechanisms Of Cell Ferroptosismentioning
confidence: 99%
“…Cystine is reduced to cysteine to participate in GSH synthesis by system Xc - ( 60 ). The transport process of this system does not require ATP, and it is mediated by the difference in the concentration of amino acids presenting on both sides of the cell membrane ( 61 ). GSH is a tripeptide comprising glutamate, cysteine, and glycine.…”
Section: Molecular Mechanisms Of Cell Ferroptosismentioning
confidence: 99%
“…As the name suggests, this programmed cell death pathway is dependent on iron, and is induced by the oxidation of polyunsaturated fatty acids (PUFAs) that are present in lipid bilayer membranes. Iron has been described to act as a catalyst in the Fenton reaction (where H 2 O 2 is converted to ·OH radicals), triggering a free-radical chain reaction and resulting in PUFA oxidation or degradation [ 72 ]. The iron-dependent oxidation of PUFAs causes mitochondrial alterations and cell membrane damage, which promotes cell death.…”
Section: Definition Of Oxidative Stress and Inflammationmentioning
confidence: 99%
“…According to models of cultured hippocampal slices of rat organs, ferroptosis was implicated to be the driving factor of neuronal death ( Dixon et al, 2012 ). Recent studies have linked ferroptosis to common diseases involving neuronal injury, such as stroke, Amyotrophic Lateral Sclerosis, Alzheimer’s disease and Parkinson’s disease ( Chen et al, 2021 ; Tan et al, 2021 ). It has also confirmed that ferroptosis exists and plays an important role in SCI.…”
Section: Tlr4 Signalingmentioning
confidence: 99%